AN EVALUATIVE STUDY OF THE POLITICAL EDUCATION PROGRAMME OF THE DIRECTORATE FOR SOCIAL MOBILISATION (MAMSER) 1987-1992 (1995)
The study evaluated the strategies employed by the Directorate for Social Mobilisation (MAMSER) for its Political Education Programme in Nigeria between 1987 and 1992. This was with a view to determining the best strategies for political education within the context of Nigerian environment. Chapter One is the Introduction to the study. A brief Historical Background of Nigerian Politics which resulted in the setting up of an agency for political education was reviewed. The chapter also contains the Need for the Study, Statement of Problem, Research Questions and the Overview of MAMSER. Chapter Two is the Conceptual Framework where concepts related to the study were examined. The concepts reviewed included Political Education, Political Culture, Mass Education, Evaluation Process and Models of Evaluation. Relevant related Literature on Political Education was reviewed. The review covered Political Education and the Society, Political Education and Mass Literacy, Political Education and Adult Education, Methodology of Political Education and Evaluation of Political Education Programme. The Descriptive Survey Research Design was adopted for the study. A set of questionnaire was designed, using a five-point Likert Scale as the instrument for the study. 800 randomly selected subjects drawn from rural and urban communities in Oyo State served as the subjects for the study. Oral interviews and records available at MAMSER'S Offices at the Local Offices and State Headquarters were used to complement the data collected' through the questionnaire from the respondents. Key figures involved in the planning and implementation of the MAMSER Political Education programme like the then Secretary to MAMSER, Professor Tunde Adeniran and the Bauchi State then Director of MAMSER, Dr. Musa Moda were interviewed. The data collected through the instrument administered to the respondents were analysed, using correlation co-efficient, chi-square and t-test statistical tools. From the study, the following findings were established. (i) MAMSER was designed to fail by the government. (ii) Most respondents were aware of the existence of MAMSER as a government organ; (iii) Most respondents did not understand the content and objectives of MAMSER's political education programme; (iv) The delivery strategies used for the propagating/disseminating the political education programme by MAMSER were not effective; (v) Most of the personnel of MAMSER were not trained adult educators with expertise of mobilising adults; (vi) There was no specified curriculum for the political education programme and (vii) There was no effective monitoring of the programme. Based on the findings, the policy implications were identified and a feasible policy for political education was recommended in Chapter Five for better political awareness in the Nigerian polity to include: (i) A framework for a political education programme in Nigeria; (ii) Training of all personnel in adult education and political education; (iii) Training in management and administration for all the cadres of MAMSER's staff; (iv) Preparation of curriculum/syllabus on political education geared towards the Nigerian environment. (v) Involvement of other Government Agencies, Ministries and Universities in the Planning, Implementation and Evaluation of the programme.